Hepatitis B incidence among South Asian children in England and Wales: implications for immunisation policy. Issue 12 (11th December 2003) - Hahné, S; Ramsay, M; Soldan, K; Balogun, K; Mortimer, P
Abstract : The incidence of acute hepatitis B virus (HBV) infection is higher among South Asian than among non-South Asian UK residents, and infections in South Asians occur more often during childhood. The UK's immunisation policy should be changed to protect ethnic minority children against HBV infection.